2017
DOI: 10.1039/c7ob02163a
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of [2H1]-(1R,2R)- and [2H1]-(1S,2R)-glycerols into the antibiotic nucleocidin in Streptomyces calvus

Abstract: Deuterium incorporations from [H]-(1R,2R) and [H]-(1S,2R) glycerols into the fluorine containing antibiotic nucleocidin, in Streptomyces calvus indicate that one deuterium atom is incorporated at the C-5' site of nucleocidin from each of these isotopomers of glycerol. Two deuteriums become incorporated at C-5' of nucleocidin after a feeding experiment with [H]-glycerol. These observations indicate that there is no obligate oxidation of the pro-R hydroxymethyl group of glycerol as it progresses through the pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Halogenated nucleosides represent an important class of synthetic drugs used in anticancer and antiviral treatments, including Cladribine ( 1 , anti‐leukaemia), Clofarabine ( 2 , anti‐leukaemia), Fludaradine ( 3 , anti‐leukaemia), Fluorouracil ( 4 , antitumor), Gemcitabine ( 5 , anticancer), and Sofosbuvir ( 6 , anti‐Hepatitis C; Figure A). In contrast, there are relatively few known halogenated nucleoside natural products, with nucleocidin ( 7 a , fluorinated at C4′ of ribose), AT‐265 ( 7 b , dealanylascamycin, chlorinated at C2 of adenosine), and adechlorin ( 8 , chlorinated at C2′ of ribose; Figure B) being rare examples. Adechlorin is the 2′‐chloro derivative of pentostatin ( 9 ), a competitive inhibitor of adenosine deaminase that is approved as a drug for leukaemia treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Halogenated nucleosides represent an important class of synthetic drugs used in anticancer and antiviral treatments, including Cladribine ( 1 , anti‐leukaemia), Clofarabine ( 2 , anti‐leukaemia), Fludaradine ( 3 , anti‐leukaemia), Fluorouracil ( 4 , antitumor), Gemcitabine ( 5 , anticancer), and Sofosbuvir ( 6 , anti‐Hepatitis C; Figure A). In contrast, there are relatively few known halogenated nucleoside natural products, with nucleocidin ( 7 a , fluorinated at C4′ of ribose), AT‐265 ( 7 b , dealanylascamycin, chlorinated at C2 of adenosine), and adechlorin ( 8 , chlorinated at C2′ of ribose; Figure B) being rare examples. Adechlorin is the 2′‐chloro derivative of pentostatin ( 9 ), a competitive inhibitor of adenosine deaminase that is approved as a drug for leukaemia treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Deuterium labels of the pro-S CH 2 OH group of glycerol, in turn, are lost, and the secondary carbon of glycerol becomes the C4′ of nucleocidin (Scheme 11). 52,53 This shows that the pro-R CH 2 OH carbon is not oxidized as glycerol, and it is progressed along the pentose phosphate pathway, incorporating into the ribose moiety of nucleocidin. 52 Note that the enzyme responsible for fluorine incorporation is still unknown.…”
Section: (2s3s)-4-fluorothreoninementioning
confidence: 99%
“…In 2015, Zechel's group reported that complementation of S. calvus ATCC13382 with a functional bldAencoded Leu-tRNA UUA molecule restores the production of nucleocidin 1 and identified the genes encoding the biosynthesis of the 5′-O-sulfamate group of the nucleocidin 1 (Zhu et al 2015). In the next year, O'Hagan's group provided the first biosynthetic data on nucleocidin 1 assembly from isotope labeling studies (Bartholomé et al 2016;Feng et al 2017). However, there was still no illumination for the mechanism of fluorination involved in this biosynthetic pathway.…”
Section: Enzyme-catalyzed C-f Bond Formationmentioning
confidence: 99%